(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
A Schiff base was prepared by the condensation of 2-aminobenzenethiol and 4-nitrobenzaldehyde. Metal (II) chlorides were refluxed with the prepared Schiff base affording the corresponding metal(II) complexes. The synthesized compounds were characterized based on T-IR, solubility test, melting point/decomposition temperature, molar conductance, magnetic susceptibility, UV-visible spectroscopy and elemental analysis. IR spectra of the Schiff base indicated the azomethine (-C=N-) peak at 1596cm-1, which is shifted in the spectra of the complexes. The Schiff base melts at 160oC, whereas the chelate decomposes within the range of (220oC -232oC). The Elemental analysis revealed the metal to ligand ratio as 1:2. Molar conductance values (11.03 -1cm2mol-1 15.93 -1cm2mol-1) showed non- electrolytic nature of the complexes, magnetic susceptibility values of the complexes were recorded at the range (4.51BM -5.85BM). The synthesized Schiff base and their respective complexes were screened for their anti-microbial activities against some selected pathogenic bacteria (Staphylococcus aureus, and Escherichia coli) and fungi (Aspergillus niger and Candida albicans), the Schiff base shows moderate activity at 6 -15mm zone of inhibition, while the metal(II) complexes show higher activity with the increased in concentration. Moreover, antifungal data revealed an appreciated activity (6 18) mm zone of inhibition against all fungal isolates, which is lower than the standard.